Carbon transfer printing : a step-by-step manual, featuring contemporary carbon printers and their creative practice /: a step-by-step manual, featuring contemporary carbon printers and their creative practice. (2019) - King, Sandy, 1952-; Nelson, Don; Lockhart, John
No abstract available